Menakar Rasa Nasionalisme Generasi Muda Indonesia (Measuring the Sense of Nationalism of Indonesian young generation) - Saripurnawan, Djunaedi (Masyarakat Indonesia, 2020)
The phenomenon of social bipolarization that occurs in the Indonesian nation in the context of the 2019 presidential election, which is between the supporters of Joko Widodo & Ma'aruf Amin who face the stronghold of Prabowo Subianto & Sandiaga Uno, is inseparable from the background of the 1998 reform era when the authoritarian militarism regime collapsed by mass action (demonstration) and students at that time. This bipolarization has a clear and negative impact, even tends to be "verbal war", "identity politic war" that uses all means through social media and reaches attitudes and social behavior. Qualitative search of the Indonesian millennials shows the declining phenomenon of awareness of the nation and state of Indonesia (NKRI) and the poor knowledge and understanding of the ideology of the country so that other understandings are easily infiltrated, even negating the ideology of the Indonesian nation: Pancasila threatens wholeness The Unitary State of the Republic of Indonesia which was built with full struggle and sacrifice of the heroes of independence. The role of the government in providing an understanding of the history and ideology of this nation is an obligation that must be carried out as well as possible through the world of education, sports, and in every dynamic of participatory and transparent development.